Understanding flame-retardant grades better - Sarabi, Bahman; Drummer, Dietmar (Kunststoffe International, 2017)
More and more applications require the use of plastics that meet defined ire safety requirements. This presupposes that the reaction to ire can be determined by reliable and reproducible test methods.
CRIS-Team Scopus Importer:2023-03-29